2021
DOI: 10.1111/obr.13380
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight and small for gestational age are associated with complications of childhood and adolescence obesity: Systematic review and meta‐analysis

Abstract: In recent decades, the incidence of type 2 diabetes (T2D) has increased dramatically in children and adolescents, posing a real public health problem. Beyond unhealthy diets and sedentary lifestyles, growing evidence suggests that some perinatal factors, such as low birth weight (LBW), are associated with higher risk of T2D in adulthood.In this regard, it remains unclear whether the increased risk is already present in childhood and adolescence. We conducted a systematic review and meta-analysis to clarify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 45 publications
2
45
1
1
Order By: Relevance
“…Previous studies have shown that LBW is closely associated with chronic metabolic diseases such as diabetes, obesity and metabolic syndrome in adult life. [ 15 , 16 ] Our previous meta-analysis also showed that LBW significantly increased the future risk of developing T2DM. [ 17 ] However, the exact mechanism of LBW causing metabolic disorders is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LBW is closely associated with chronic metabolic diseases such as diabetes, obesity and metabolic syndrome in adult life. [ 15 , 16 ] Our previous meta-analysis also showed that LBW significantly increased the future risk of developing T2DM. [ 17 ] However, the exact mechanism of LBW causing metabolic disorders is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Upon further investigation, our studies have suggested poor trophoblast invasion, 22 impaired fetoplacental blood perfusion, 23 and placental dysfunction 24 as critical events in the pathogenesis of ozone‐induced reductions in fetal weight. Importantly, prenatal growth restriction and exposure to air pollutants have been independently associated with an increased risk of metabolic disease in childhood 12,25 . Hence, we hypothesize that ozone‐induced FGR is likely to program a heightened risk to obesity and metabolic disease in adulthood.…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, prenatal growth restriction and exposure to air pollutants have been independently associated with an increased risk of metabolic disease in childhood. 12,25 Hence, we hypothesize that ozone-induced FGR is likely to program a heightened risk to obesity and metabolic disease in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ICS is often the hub of multiple environmental stressors, while pregnancy and newborn stages are identified as the most susceptible life stages with high risks for health effects [ 5 , 6 , 7 ]. ABOs are considered a serious public health problem as they increase the probability of short- and long-term health consequences, including chronic diseases in later life stages [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%